Assessment of Total Phenolic and Flavonoid Content from Nine Different Families of Herbal Medicines Originated from West Java, Indonesia - Hasanah, Aliya Nur (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Indonesia is known as a country with abundant natural resources, one of which is herbal plants. These herbal plants contain secondary metabolites such as polyphenol and flavonoid that have some health advantages. The amounts of these two chemicals can be measured using the UV-visible spectrophotometric method, with gallic acid for polyphenols and quercetin for flavonoids as reference standards. In this study, 18 herbal plants from 9 different families were used to calculate the total phenolic content calculated as gallic acid and the total flavonoid content calculated as quercetin. Quantitative analysis was calculated using a UV-Visible spectrophotometry instrument. Meanwhile, qualitative analysis was observed using thin layer chromatography (TLC). The result shown that five plant extracts from Lauraceae, Fabaceae, Myrtaceae, and Melastomataceae family were obtained which had the highest total phenolic content, namely cinnamon cortex (Cinnamomum burmannii), angsana leaves (Pterocarpus indicus Willd.), bay leaves (Syzygium polyanthum (Wight.) Walp.), harendong bulu leaves (Clidemia hirta (L.) D. Don), and clove leaves (Syzygium aromaticum L.) with respective levels of 2120.00; 2056.19 ; 2049.52 ; 1989.52 and 1837.14 mgGAE/g. Meanwhile, the five plant extracts from Zingiberaceae, Fabaceae, and Lamiaceae family that had the highest total flavonoid levels were red ginger (Zingiber officinale cv rubra), temu ireng (Curcuma aeruginosa), temu giring (Curcuma heyneana), gayam leaves (Inocarpus fagiferus Fosb.), and nilam leaves (Pogostemon cablin Benth.) with respective levels of 130.47; 125.74; 107.91 ; 82.89 and 79.25 mgQE/g